2008
DOI: 10.2116/analsci.24.735
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Gradient Capillary Electrochromatography by Varying the Mobile Phase Composition and Applied Voltage

Abstract: Dual-gradient capillary electrochromatography (DG-CEC) was developed to provide superior performance with regard to the separation of ionized analytes; in this method, both the eluent composition and the applied voltage are varied during the separation procedure. As for the gradient in the eluent composition, a shift in the pH is employed to control not only the electrophoretic mobility, but also the retention factor of the analytes. The dual-gradient method was shown to be effective in increasing the resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In this condition, the cationic peptides migrated toward the outlet, in which ACN content was relatively higher and the interaction with the stationary phase was slightly enhanced. The electrophoretic migration in the linear gradient field would reduce the peak width in a similar fashion to our previous studies .…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…In this condition, the cationic peptides migrated toward the outlet, in which ACN content was relatively higher and the interaction with the stationary phase was slightly enhanced. The electrophoretic migration in the linear gradient field would reduce the peak width in a similar fashion to our previous studies .…”
Section: Resultssupporting
confidence: 65%
“…As a consequence, the analyte at the front end was overtaken by that at rear end and the peak width was reduced, or focused. However, in our previous study, the magnitude of the reduction in the peak width was approximately half at the maximum, or the peak height increased approximately twice as much .…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…12 Therefore, on-capillary concentration methods for CE should be applicable to pCEC and may be potentially useful for reducing the sample zone width spread in the column. 13,14 Recently, we reported on analyte zone sharpening for angiotensins in hydrophilic interaction capillary electrochromatography using a mobile phase containing perchloric acid. 15 In this previous study, we revealed that the gradient elution provided a significantly high conductive zone, which was produced by desorption of perchloric anions from the stationary phase.…”
Section: Introductionmentioning
confidence: 99%